Bahasa Inggis - Ipambonj, Lisa; Kamal, Mohammad Mukhlis; Taryono, Taryono; Mana, Ralph (Coastal and Ocean Journal (COJ), 2025)
This study examines community perceptions and involvement in coral reef conservation in Awaiama Village, Milne Bay Province, Papua New Guinea, through a social-ecological framework. Fieldwork in October 2024 integrated coral reef assessments with semi-structured interviews involving local stakeholders. Results indicate that coral reefs are important to livelihoods, food security, and cultural heritage. Despite this dependency, the reefs are increasingly threatened by overfishing, destructive fishing practices, and the impacts of climate change. The community exhibits limited ecological awareness and continues relying on unsustainable fishing methods. Although minor signs of reef recovery were recorded in some areas, community participation in formal conservation initiatives remains minimal. Traditional governance structures, such as clan meetings, play a more prominent role in local resource management. However, there is strong support for reef protection and recognition of the value in integrating traditional ecological knowledge with science-based management strategies. The findings highlight the need for co-management approaches tailored to local socio-economic contexts and emphasize education, sustainable practices, and collaborative governance to ensure long-term reef resilience.